The impact of entrepreneurship on knowledge economy in Africa - Simplice A. Asongu; Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2015)
Purpose - The paper assesses how entrepreneurship affects knowledge economy (KE) in Africa. Design/methodology/approach - Entrepreneurship is measured by indicators of starting, doing and ending business. The four dimensions of the World Bank's index of KE are employed. Instrumental variable panel fixed effects are applied on a sampled of 53 African countries for the period 1996-2010. Findings -The following are some findings. First, creating an enabling environment for starting business can substantially boost most dimensions of KE. Second, doing business through mechanisms of trade globalisation has positive effects from sectors that are not ICT and High-tech oriented. Third, the time required to end business has negative effects on KE. Practical implications - Our findings confirm the narrative that the technology in African countries at the moment may be more imitative and adaptive for reverse-engineering in ICTs and high-tech products. Given the massive consumption of ICT and high-tech commodities in Africa, the continent has to start thinking of how to participate in the global value chain of producing what it consumes. Originality/value - This paper has a twofold motivation. First, given the ambitions of African countries of moving towards knowledge based economies, the line of inquiry is timely. Second, investigating the nexus may have substantial poverty mitigation and sustainable development implications. These entail inter alia: the development of technology with value-added services; enhancement of existing agricultural practices; promotion of conditions that are essential for competitiveness and adjustment of globalization challenges.
Keywords: L59; O10; O30; O20; O55; 330; Entrepreneurship; Knowledge Economy; Development; Africa